The Water Histories of Hungary's Major Rivers - Ferenc Jankó; Priszcilla Hafenscher (Historica, 2023)
Taking a biographical approach, two main characters of Hungarian water‑environmental history are explored in this study. Before the global warming era, meteorologist Antal Réthly played a major role in the climatic controversy concerning the water regulation and afforestation of the Great Hungarian Plain arguing that these human activities could not change the climate. In turn, water engineer Emil Mosonyi strove to conceptualize and develop the utilization of Hungarian hydropower potentials and remained a supporter of large hydropower projects even after his emigration and return, when the construction of the Danube barrage system catalyzed the Hungarian environmental movement and the political transition in 1989. Their histories help understanding of the limited capacities of science in solving environmental controversies.